1997
DOI: 10.1046/j.1526-4610.1997.3706396.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Branch Retinal Infarcts in Association With Migraine

Abstract: Migraine has been blamed for a variety of temporary and permanent visual complications. We describe the case of a young woman with migraine who suffered recurrent episodes of retinal infarction, one of which occurred during an attack of migraine. The infarctions resulted from occlusions of branches of the central retinal artery Extensive laboratory and radiological investigations failed to establish a nonmigrainous etiology. In some individuals, migraine may cause or promote branch retinal vaso-occlusion and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…Glenn et al 31 reported a case of complicated migraine due to bilateral retinal infarction. Beversdof et al 32 reported recurrent branch retinal infarcts in association with migraine. On the other hand, the reported prevalence of cerebral WML in migraineurs ranges from 4% to 59% in selected studies.…”
Section: Discussionmentioning
confidence: 99%
“…Glenn et al 31 reported a case of complicated migraine due to bilateral retinal infarction. Beversdof et al 32 reported recurrent branch retinal infarcts in association with migraine. On the other hand, the reported prevalence of cerebral WML in migraineurs ranges from 4% to 59% in selected studies.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Retinal alterations described in the literature manifest as acute and chronic retinal damage. Migraine can lead to focal decrease in cerebral blood flow and perhaps in retinal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Using colour Doppler imaging, Kara et al 13 reported that central retinal artery and posterior ciliary artery vessel resistance was higher in patients with migraine in both headache and headache-free periods compared with the control group. All of these studies support the hypothesis of low perfusion and vascular retinal variations in migraine.…”
Section: Discussionmentioning
confidence: 99%
“…It could be recurrent (Barak et al, 1997;Beiran et al, 1995;Beversdorf et al, 1997;Johnson et al, 1994). Most of these cases probably have Susac's syndrome (autoimmune endotheliopathy leading to encephalopathy, BRAO and hearing loss) (Susac et al, 2007).…”
Section: Pathophysiology and Histologymentioning
confidence: 99%